Application of quaternary ammonium compounds as compatibilizers for polymer blends and polymer composites—a concise review - Shamsuri, Ahmad Adlie; Md. Jamil, Siti Nurul Ain (Multidisciplinary Digital Publishing Institute, 2021)
A wide variety of quaternary ammonium compounds (QACs) have escalated the attraction of researchers to explore the application of QACs. The compounds have frequently been synthesized through alkylation or quaternization of tertiary amines with alkyl halides. Recently, QACs have been applied to compatibilize polymer blends and polymer composites in improving their thermo-mechanical properties. This concise review concentrates on the application of two types of QACs as compatibilizers for polymer blends and polymer composites. The types of QACs that were effectively applied in the blends and composites are quaternary ammonium surfactants (QASs) and quaternary ammonium ionic liquids (QAILs). They have been chosen for the discussion because of their unique chemical structure which can interact with the polymer blend and composite components. The influence of QASs and QAILs on the thermo-mechanical properties of the polymer blends and polymer composites is also described. This review could be helpful for the polymer blend and polymer composite researchers and induce more novel ideas in this research area.